Wine industry perceptions and reactions to the COVID‐19 crisis in the Old and New Worlds: Do business models make a difference?. Issue 4 (25th May 2022) - Niklas, Britta; Cardebat, Jean‐Marie; Back, Robin M.; Gaeta, Davide; Pinilla, Vicente; Rebelo, João; Jara‐Rojas, Roberto; Schamel, Guenter
Abstract: The COVID‐19 crisis has severely impacted the wine industry, with producers in different countries affected differently and, therefore, differing in their perceptions toward it. These differing perceptions are assumed to be due to different business models, mainly linked to the distribution system adopted and resulting in varying distances of producers to distributors and consumers. While upstream integration characterizes the Old World, the New World applies a downstream business model, being more closely linked to distributors and consumers and, therefore, more vulnerable to shocks, which should lead to higher perceived impacts of the COVID‐19 crisis. This study analyzes 542 surveys collected from wineries in nine countries, divided into New World, historical Old World, and emerging Old World. Econometric results show statistically significant differences in both the perceived impact of COVID‐19 and wineries' responses in terms of planned investments, with the New World being more affected. A common desire by wineries to direct future investments towards direct‐to‐consumer sales and communication was found, to the detriment of investments in vineyards and cellars. This desire is particularly strong in the New World, in line with their focus on the downstream part of the value chain, underlying their greater reactivity to shocks and capacity to innovate. [EconLit Citations: D22; L21; L66; Q13].